2020
DOI: 10.1186/s12885-020-6553-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune classification for the PD-L1 expression and tumour-infiltrating lymphocytes in colorectal adenocarcinoma

Abstract: Background: Colorectal adenocarcinoma is the third most common cancer worldwide and a leading cause of cancerrelated death. The recent emergence of diverse immunotherapeutic agents has made it crucial to interpret a complex tumour microenvironment intermingled with tumour-infiltrating immune cells to predict the immunotherapeutic response rate. However, in colorectal adenocarcinoma, studies are lacking that provide detailed analyses of programmed death-ligand 1 (PD-L1) and tumour-infiltrating lymphocytes (TIL)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
(37 reference statements)
1
22
0
Order By: Relevance
“…This contrasts with known strong immunogenic tumours such as skin melanoma, renal cell and bladder cancer or head and neck and lung SCC, where TMIT I characterizes 40-50% of cases [21]. On the other hand, ITAC is comparable to adenocarcinomas of other organs such as lung, colon and stomach, with reports of 12-14%, 19% and 23% TMIT I, respectively [21,28,37,38].…”
Section: Discussionmentioning
confidence: 68%
“…This contrasts with known strong immunogenic tumours such as skin melanoma, renal cell and bladder cancer or head and neck and lung SCC, where TMIT I characterizes 40-50% of cases [21]. On the other hand, ITAC is comparable to adenocarcinomas of other organs such as lung, colon and stomach, with reports of 12-14%, 19% and 23% TMIT I, respectively [21,28,37,38].…”
Section: Discussionmentioning
confidence: 68%
“…Responses to immune checkpoint inhibitors correlated with PD-L1 expression ( Salem et al, 2018 ). Studies have demonstrated that relatively high PD-L1 expression in cancer cells was associated with a good prognosis in CRC patients ( Wyss et al, 2019 ; Noh et al, 2020 ). The high expression of PD-L1 and CTLA4 in the low-risk group not only demonstrated that the IGBRS is an efficient classifier of risk stratification in CRC and closely related to tumor immunity but also suggested that the IGBRS may be a reference for the classification of CRC patients treated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…For profiling analysis of PD-L1 expression, the proportion of PD-L1-positive tumor cells (TCs) or immune cells were quantified. Light microscopy (20) was used for the semiquantitative assessment for PD-L1 immunoreactivity. Membranous immunostaining was interpreted according to the proportion and intensity of positive tumor cells.…”
Section: Histochemistry For Pd-l1 and Cd8 Analysismentioning
confidence: 99%